2013
DOI: 10.5194/cp-9-525-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Late Cretaceous and Cenozoic climate by variable drawdown of atmospheric <i>p</i>CO<sub>2</sub> from weathering of basaltic provinces on continents drifting through the equatorial humid belt

Abstract: Abstract. The small reservoir of carbon dioxide in the atmosphere (pCO2) that modulates climate through the greenhouse effect reflects a delicate balance between large fluxes of sources and sinks. The major long-term source of CO2 is global outgassing from sea-floor spreading, subduction, hotspot activity, and metamorphism; the ultimate sink is through weathering of continental silicates and deposition of carbonates. Most carbon cycle models are driven by changes in the source flux scaled to variable rates of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 160 publications
4
63
1
Order By: Relevance
“…In detail, Kent and Muttoni (2008) suggested that the Indian plate dominated this "carbonate subduction factory", with a major decrease in CO 2 production as India and Asia collided some 50 Ma ago. However, the same authors recently concluded for low CO 2 outgassing at the Tethyan arc, mainly as a result of low decarbonation during subduction (Kent and Muttoni, 2013). For Kent and Muttoni (2013), high CO 2 could be explained by less efficient weathering close to the EECO, rather than by additional CO 2 production.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In detail, Kent and Muttoni (2008) suggested that the Indian plate dominated this "carbonate subduction factory", with a major decrease in CO 2 production as India and Asia collided some 50 Ma ago. However, the same authors recently concluded for low CO 2 outgassing at the Tethyan arc, mainly as a result of low decarbonation during subduction (Kent and Muttoni, 2013). For Kent and Muttoni (2013), high CO 2 could be explained by less efficient weathering close to the EECO, rather than by additional CO 2 production.…”
Section: Introductionmentioning
confidence: 96%
“…However, the same authors recently concluded for low CO 2 outgassing at the Tethyan arc, mainly as a result of low decarbonation during subduction (Kent and Muttoni, 2013). For Kent and Muttoni (2013), high CO 2 could be explained by less efficient weathering close to the EECO, rather than by additional CO 2 production.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations